G163(P) Recurrent Lower Respiratory Tract Infection (LRTI) in Children with Repaired Tracheoesophageal Fistula (TOF). (4th June 2013) - Nasrallah, B; Jaffray, B; Moss, S
Abstract : Aim: To identify if patients with repaired TOF have increased risk of recurrent LRTI. Methods: We reviewed the medical records of all children who had repaired TOF over the last 20 years (1990–2011) in our centre. We identified the children who presented with recurrent LRTI. We reviewed their medical records and radiological tests and findings. Results: 82 children had repaired TOF over 20 years period. Age range from 1 – 20 years old post repair period. 18 children (22%) had recurrent LRTI and needed regular courses of antibiotics. 10 out of 18 children had high resolution CT scan (HRCT) of the chest and 3 of them (4%) had confirmed bronchectasis. Conclusion: While tracheomalacia is a well recognised complication of TOF repair, there is paucity of data regarding the increased risk of LRTI. One recent study demonstrated increased cough with sputum production and chronic bronchitis in repaired TOF. (Acta Paediatr. 2011 Sep; 100(9):1222–5). In our study we found increased risk of recurrent LRTI in children with repaired TOF (one fifth of the patients). The incidence of bronchectasis was 4%. These findings highlights the importance of awareness of the long-term respiratory complications in children with repaired TOF.